The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1097/adm.0000000000000381
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Effectiveness of Continuing Methadone Maintenance Treatment During Incarceration Compared With Forced Withdrawal

Abstract: Results support interventions that facilitate continuity of MMT during and after incarceration. Engagement of a community provider is feasible and can improve access to methadone in correctional facilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 28 publications
(30 reference statements)
1
17
0
Order By: Relevance
“…Fourteen studies assessed the impact of OAT provision while incarcerated (Table 3). Seven of these studies were experimental [5662], and 7 were observational [26,6368]. Eight studies evaluated the impact of receiving OAT—primarily methadone—while incarcerated compared to opioid detoxification [26,6064,67,68], and 2 studies evaluated the impact of methadone dose at the time of release [65,66].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fourteen studies assessed the impact of OAT provision while incarcerated (Table 3). Seven of these studies were experimental [5662], and 7 were observational [26,6368]. Eight studies evaluated the impact of receiving OAT—primarily methadone—while incarcerated compared to opioid detoxification [26,6064,67,68], and 2 studies evaluated the impact of methadone dose at the time of release [65,66].…”
Section: Resultsmentioning
confidence: 99%
“…Multiple studies have found that individuals with OUD who receive MMT during their incarceration period are more likely to access, initiate, and adhere to addiction treatment post-release, compared with individuals who do not receive MMT during their incarceration [6062]. Findings from the RCT conducted by Brinkley-Rubinstein et al [61] also indicated that those who were assigned to tapered withdrawal from methadone after the first week of incarceration were significantly more likely to experience a nonfatal overdose during the 12-month follow-up period, compared to those who received MMT while incarcerated (OR = 2.83, 95% CI 1.05–7.61, p < 0.05).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, as participants noted, incarceration could prevent or interrupt PrEP utilization among PWID by disconnecting individuals from regular sources of healthcare and social services. Novel intervention strategies are needed to provide PrEP during criminal justice system involvement and following release from incarceration, a period when injection-related risk behaviors for HIV acquisition are known to be high [ 64 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Opioid treatment programs, most notably the APT Foundation in New Haven, have expanded evidence-based treatment for OUD by adopting open access models that eliminate waiting lists and shorten intake times to 90 min [22]. Methadone treatment has been expanded to incarcerated persons in six of the state's correctional facilities, beginning with the jails in New Haven in 2013 and in Bridgeport the following spring [23]. Treatment in correctional facilities has been complemented by efforts of the Department of Corrections, which have reduced the incarcerated census by one-third between 2010 and 2019 [24].…”
Section: Introductionmentioning
confidence: 99%